Mobilization of Stem Cells Using G-CSF for Acute Ischemic Stroke: A Randomized Controlled, Pilot Study - Kameshwar Prasad; Amit Kumar; Jitendra Kumar Sahu; M. V. P. Srivastava; Sujata Mohanty; Rohit Bhatia; Shailesh B. Gaikwad; Achal Srivastava; Vinay Goyal; Manjari Tripathi; Chandrashekar Bal; Nalini Kant Mishra (Stroke Research and Treatment)
Background. There is emerging evidence to support the use of granulocyte colony-stimulating factor (G-CSF) therapy in patients with acute ischemic stroke. Aims. To explore feasibility, safety, and preliminary efficacy of G-CSF therapy in patients with acute ischemic stroke. Patients and Method. In randomized study, 10 patients with acute ischemic stroke were recruited in 1 : 1 ratio to receive 10 μg/kg G-CSF treatment subcutaneously daily for five days with conventional care or conventional treatment alone. Efficacy outcome measures were assessed at baseline, one month, and after six months of treatment included Barthel Index (BI), National Institute of Health Stroke Scale, and modified Rankin Scale. Results. One patient in G-CSF therapy arm died due to raised intracranial pressure. No severe adverse effects were seen in rest of patients receiving G-CSF therapy arm or control arm. No statistically significant difference between intervention and control was observed in any of the scores though a trend of higher improvement of BI score is seen in the intervention group. Conclusion. Although this study did not have power to examine efficacy, it provides preliminary evidence of potential safety, feasibility, and tolerability of G-CSF therapy. Further studies need to be done on a large sample to confirm the results.